Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Sistem Persamaan Linier Tiga Variabel di Kelas X - Arnold S. O. Sihombing; Ropinus Sidabutar; Suprapto Manurung (Journal on Education, 2023)
In the learning process students often do not understand the math problem being worked on, so the steps for solving it are not appropriate. This is caused by the students' mathematical problem solving abilities which are still low and the learning model used by the teacher is still not appropriate for students' mathematical problem solving abilities. This study aims to determine the effect of the Problem Based Learning (PBL) model on students' mathematical problem solving abilities on the material system of three variable linear equations in class X. This study used a quantitative method with a quasi-experimental research type and used a Pre-test Post-test Control Group Design. The population of this study were all students of class X and the sample was taken by Cluster Random Sampling with 2 classes, namely the experimental class (X-1) and the control class (X-2). The instrument used is a description test of 5 questions and observation. This data analysis uses prerequisite test and hypothesis test with t-test. From the results of the study, the average Post-Test value of the experimental class was 78.68 and the average Post-Test value of the control class was 70.74. Judging from the average value of students' mathematical problem solving abilities between the experimental class and the control class, it can be concluded that the Problem Based Learning (PBL) model has a higher influence than conventional learning. Based on the hypothesis test using the t-test, the result is that tcount>ttable=2.123>2.016 with a significant level of 5%, then H0 is rejected and Ha is accepted. So that it can be concluded that there is an influence of the Problem Based Learning (PBL) model on students' mathematical problem solving abilities in the three-variable linear equation system material in class X.